2006
DOI: 10.1038/sj.eye.6702446
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two acrylic intraocular lenses with different haptic designs in patients with combined phacoemulsification and pars plana vitrectomy

Abstract: Purpose The intra-and postoperative characteristics of two foldable single-piece intraocular lenses (IOL) with identical hydrophilic acrylic material, but different haptic designs (Akreos Adapt s and Akreos Fit s ), were compared in combined phacoemulsification and pars plana vitrectomy (PPV). Methods This was a prospective, randomized study in patients with simultaneous cataract and vitreoretinal surgery. Group A (n ¼ 47 patients) included implantation of Akreos Fit s IOL (two-point haptic) and group B (n ¼ 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
(13 reference statements)
0
13
0
Order By: Relevance
“…The four-haptic IOLs may provide a large IOL surface in contact with posterior capsule and a more accurate IOL fixation in the capsular bag, leading to a constant tension on the zonular fibers and less myopic shift [12,32]. This led to the assumption of this study that the stability of four-haptic IOL lessens anterior capsule contraction, but the haptic number and design were not strongly related to anterior capsule contraction.…”
Section: Discussionmentioning
confidence: 99%
“…The four-haptic IOLs may provide a large IOL surface in contact with posterior capsule and a more accurate IOL fixation in the capsular bag, leading to a constant tension on the zonular fibers and less myopic shift [12,32]. This led to the assumption of this study that the stability of four-haptic IOL lessens anterior capsule contraction, but the haptic number and design were not strongly related to anterior capsule contraction.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we focused on the number and position of the haptics in the circular zonule, because ACO may be caused by LEC growth, whereas ACC is accelerated by the difference between the centripetal force of the anterior capsule opening margin (fibrotic force) and the centrifugal force of the capsular zonule [ 18 , 19 ]. Some studies have suggested that four-haptic IOLs confer a large surface that contacts the posterior capsule, as well as more accurate IOL fixation within the capsular bag, leading to constant tension on the zonular fibers [ 28 ]. However, later studies reported that the number and design of haptics were not strongly associated with ACC [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with 25-gauge phacovitrectomy, more frequent IOL decentration has been observed with 20-gauge vitrectomy combined with phacofragmentation [ 46 ]. Better centration has been recorded with a 4-point haptic design IOL compared with an intraocular lens incorporating a 2-point haptic design [ 47 ]. In a comparative study, Leiderman et al [ 48 ] revealed that single-piece acrylic IOLs are associated with a low rate of surgical complications after combined phacovitrectomy.…”
Section: Discussionmentioning
confidence: 99%